Representation of Male and Female Characters in Cerita Pendek Tentang Cerita Cinta Pendek: A Transitivity Analysis - Windi Noor Auliani Putri (Passage, 2018)
This study is aimed at investigating the representation of male and female characters in the three short stories of Cerita Pendek tentang Cerita Cinta Pendek and revealing hidden meanings embedded in the representations by identifying the process type choices. This study employs a qualitative method and transitivity analysis proposed by Fairclough’s three-dimensional approach (1989) and Halliday’s transitivity (2004). Based on the analysis, all six process types of transitivity are embedded to male and female characters in which females have the highest number. It means that the short stories tend to represent male characters as a more passive participant while female characters as a more active and powerful participant. This study also finds that the female characters are still victimized by the male characters sexually and violently. The study suggests that the author intended to openly discuss the sexuality issue in Indonesian contexts from females’ perspective. Keywords: Transitivity, Critical Discourse Analysis, Language and Gender, Literary Texts, Representation